Experimental Study on the Use of the Modifying Agent for Expansive Soil Stabilization: Mockup Test on a Case Study - Hoang Minh, Dang; Thi Nien, Nguyen (International Journal of Sustainable Construction Engineering and Technology, 2022)
To improve the soft grounds, soil stabilization has been used widely in many tropical countries including Vietnam. This paper presents the experimental study on the use of the modifying agent for expansive soil stabilization. A real-scale one-kilometer rural road was used for the experimental test. It was divided into four parts, and each part was subjected to different stabilization tests. The specimens extracted from every quarter were denominated as Q1 (soil + cement), Q2 (soil + cement + fly ash), Q3 (soil + cement + fly ash + modifying agent) and Q4 (soil + cement + modifying agent). The assessment test showed that specimen Q1 yielded the highest water absorption percentage after 24 hours and 72 hours of soaking. The longer the soaking time, the more water diffusion occurred at specimens Q1 and Q2 rather than at specimens Q3 and Q4. When subjected to the unconfined compressive and indirect tensile tests, specimens Q1 and Q3 yielded the lowest and highest strength, respectively. The use of the modifying agent in the specimens Q3 and Q4 has improved noticeably unconfined compressive strength, indirect tensile strength, and water stability compared to the specimens Q1 and Q2. However, ettringite-based sulfate heaving might be exhibited with the use of fly ash, this may cause damage to the overlying pavement structure in the long term. Therefore, to improve the expansive soil stabilization using the modifying agent, it is recommended to use the constituent materials in specimen Q4 rather than in Q3.